SUSTAINABLE CULTURAL TOURISM IN THE ERA OF SUSTAINABLE DEVELOPMENT - Sihombing, Irene Hanna H.; Suastini, Ni Made; Puja, Ida Bagus Putu (Politeknik Pariwisata NHI Bandung, 2024)
Cultural sustainability has recently emerged as a significant trend in the tourism industry, driven by increased awareness of travel's environmental impacts and the need to preserve natural resources for future generations. Sustainable cultural tourism emphasizes protecting and valuing cultural heritage while ensuring that tourism activities respect the environment and the integrity of local cultures. For it to be genuinely comprehensive, sustainable cultural tourism must be integrated into national development strategies, aligning tourism goals with broader sustainable development objectives. Cultural tourism plays a unique role as both a catalyst and enabler of sustainable development, fostering economic resilience, social cohesion, and environmental conservation. This paper explores the relationship between cultural tourism and sustainability by examining how sustainable cultural tourism supports sustainable development goals. Essential to this approach is preserving and managing cultural heritage, involving local communities in decision-making, promoting effective conservation practices, supporting rural development, and addressing issues like over-tourism, which can lead to the loss of authenticity and over-concentration in popular destinations. Ultimately, sustainable cultural tourism is not only about conserving the past but also about creating a harmonious relationship between culture and tourism that benefits present and future generations. Through its focus on local empowerment, responsible resource use, and respect for cultural diversity, sustainable cultural tourism offers a forward-looking approach, ensuring that tourism continues to drive positive social and environmental change.